Leis e costumes da cultura de Nuzi e suas possíveis relações com os substratos narrativos tradicionais dos patriarcas e matriarcas bíblicos - Paula, Ricardo Almeida de (2003)
The present research is destined to study a group of laws of the ancient Near East in relationship with patriarchal and matriarchal biblical accounts. Scholars just like E.A. Speiser and Cyrus Gordon agree that exists some narrow relationship of this material found at Nuzi and the patriarchal and matriarchal modus vivendi, although, Thomas L. Thompson and John Van Seters argued against the value of such material asserting the non-relationship as just thought in the beginning of the research and the Kirkuk findings. We selected some passages for critical studies, in the way to put in order the sides of the question and realize the relationship in broader sense with legal corpus of the ancient Near East.